Harold A. Armold papers - Armold, Harold A.
Notes regarding experiences on the Bataan Death March, Philippines, written by Armold at Zentsuji prisoner-of-war camp, Shikoku Island, Japan, in early 1943. Includes a typewritten transcript of the notes and remarks written by Armold in 1967.
Soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bataan Death March, Philippines, 1942.; World War, 1939-1945 -- Concentration camps -- Philippines; World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Prisoners and prisons, Japanese; Soldiers